Effectiveness of reducing corneal astigmatism after combined high-frequency LDV Z8 femtosecond laser-assisted phacoemulsification and arcuate keratotomy - Lin, Hung-Yuan; Chen, Shuan; Chuang, Ya-Jung; Zhang, Suhua; Chang, Steven Wei-Hsin; Lin, Pi-Jung; Zhang, Zhe (Frontiers in Cell and Developmental Biology, 2022)
Purpose: In this retrospective study, we aimed to investigate the efficacy of the FEMTO LDV Z8 femtosecond laser-assisted cataract surgery (Femto Z8 FLACS) and femtosecond laser arcuate keratotomy (FSAK) in reducing corneal astigmatism. Methods: Using the FEMTO LDV Z8 laser, FSAK was placed at a diameter of 8.5 mm with a depth of 80% during FLACS. Pentacam measured corneal astigmatism before and 3 months after surgery. Multiple regression analysis was used to evaluate the factors contributing to the effectiveness of FSAK. Vector analyses were performed. The with-the-wound and against-the-wound changes were calculated along the meridian of the FSAKs to obtain the net corneal changes. Results: The study included 80 eyes from 62 patients. The preoperative mean keratometric astigmatism was 0.92 ± 0.44 diopters (D). Three months after FSAK, the mean keratometric astigmatism significantly reduced to 0.61 ± 0.45 D compared with preoperative corneal astigmatism (P <.05). Moreover, the percentages of eyes with ± 0.5 D and ± 1.0 D of astigmatism significantly decreased 3 months postoperatively by 58% and 85%, respectively (P <.05). Conclusion: The FEMTO LDV Z8 laser can create effective precise arcuate keratotomy with an excellent safety profile, rapid recovery, and vision stability.